Impact of Social Forestry Program Forest Partnership Scheme on Forest Sustainability and Forest Farmer Income - Djoko Setyo Martono (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2020)
One of the Government's efforts to create a prosperous society, sustainable forests, and maintained food security in Indonesia is the issuance of Minister of Environment and Forestry Regulation No. 83/2016, Concerning Social Forestry. Social Forestry (Social Forestry) is a system in the management of forest resources in state and private forests by involving communities around the forest as the main actors in forest management. This research is conducting to determine the impact of the Forestry Partnership Scheme Social Forestry Program on forest conservation and forest farmer income. The Social Forestry Program has a good impact on forest sustainability and the income of forest farmers. In 2017-2019 the high level of involvement of LMDH and farmers can support the success of crops with a value of 90-97% or tremendous growth, for overcoming forest and fire security disturbances. In 2019, the involvement of Farmers and LMDH was very high in 6 times a year, supporting the small number of forest security disturbances that only occurred four times with a loss of only Rp. 7,012,000, and can reduce the area of forest fires from 17 Ha to 4 Ha. In the income sector, through the PS program of the forestry partnership scheme, the average net income of farmers in a year is Rp. 324,950,000 or 62.5% of the total gain and Rp. 195.510.00 or 37.5% obtained from other sources of income (livestock, trading, and other jobs).